2023
DOI: 10.3390/ijerph20043258
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Vegan, Vegetarian, and Omnivore Diet Quality and Depressive Symptoms in Adults: A Cross-Sectional Study

Abstract: Dietary patterns and depressive symptoms are associated in cross-sectional and prospective-designed research. However, limited research has considered depression risk related to meat-based and plant-based dietary patterns. This study explores the association between diet quality and depressive symptoms across omnivore, vegan, and vegetarian dietary patterns. A cross-sectional online survey utilised the Dietary Screening Tool (DST) and the Centre for Epidemiological Studies of Depression Scale (CESD-20) to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…Some biological factors include decreased monoamine function, dysfunctional hypothalamic pituitary adrenal (HPA) axis, neuro‐progression/brain plasticity, mitochondrial disturbances (Lopresti et al, 2013; Pereira et al, 2020), cytokine‐mediated inflammatory processes, increased oxidative stress, immune responses (Berk et al, 2013), immuno‐inflammation, gut dysbiosis and gut/brain relationship (Kaplan et al, 2015; Pereira et al, 2020). While these biological factors play a role in the experience of depressive symptoms, they are also influenced by a diet rich in plant‐based foods such as fruit and vegetables (Bayes et al, 2021; Daneshzad et al, 2020; Nguyen et al, 2017; Walsh et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Some biological factors include decreased monoamine function, dysfunctional hypothalamic pituitary adrenal (HPA) axis, neuro‐progression/brain plasticity, mitochondrial disturbances (Lopresti et al, 2013; Pereira et al, 2020), cytokine‐mediated inflammatory processes, increased oxidative stress, immune responses (Berk et al, 2013), immuno‐inflammation, gut dysbiosis and gut/brain relationship (Kaplan et al, 2015; Pereira et al, 2020). While these biological factors play a role in the experience of depressive symptoms, they are also influenced by a diet rich in plant‐based foods such as fruit and vegetables (Bayes et al, 2021; Daneshzad et al, 2020; Nguyen et al, 2017; Walsh et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study reported very low levels of omega-3 polyunsaturated fatty acids in vegetarians and vegans [ 56 ]. This reduction in omega-3 polyunsaturated fatty acid intake among some vegetarians may be due, in part, to the fact that the primary bioavailable source of these fatty acids is oily fish [ 57 ]. Deficiencies in these fatty acids could have a negative impact on mental health, brain function, and the modulation of neurotransmitters responsible for mood; this, in turn, could lead to anxiety [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…13 The causes of non-communicable diseases and mental disorders involve a complex interplay between predisposing risk factors and various lifestyle, environmental and health-related exposures. [14][15][16] Moreover, a significant inter-relationship exists between non-communicable diseases and mental disorders. Therefore, to gain novel insights into the causes and consequences of noncommunicable diseases and mental disorders, large prospective studies that comprehensively collect diverse exposures prior to the onset of diseases are essential.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The causes of non-communicable diseases and mental disorders involve a complex interplay between predisposing risk factors and various lifestyle, environmental and health-related exposures 14–16. Moreover, a significant inter-relationship exists between non-communicable diseases and mental disorders.…”
Section: Introductionmentioning
confidence: 99%